2006
DOI: 10.1039/b506241a
|View full text |Cite
|
Sign up to set email alerts
|

Practical control of SERRS enhancement

Abstract: The demonstration that quantitative and sensitive analysis can be carried out using surface enhanced resonance Raman scattering (SERRS) prompted a discussion and investigation of the main variables which are within the control of the analyst using colloidal silver as the substrate. Previous papers have dealt with the crucial need to obtain good chemisorption of the analyte to the surface and have reported the use of specially designed dyes for SERRS. One of the most variable processes is the aggregation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 27 publications
3
67
0
Order By: Relevance
“…[3][4][5] An alternative method to provide greater control over the aggregation and assembly state of the nanoparticles is to use a DNA templated approach. This has previously been used to assemble nanoparticles in a number of different studies [6][7][8][9] but only recently to investigate the enhancement of the SERS effect.…”
Section: Mixed Metal Nanoparticle Assembly and The Effect On Surface mentioning
confidence: 99%
“…[3][4][5] An alternative method to provide greater control over the aggregation and assembly state of the nanoparticles is to use a DNA templated approach. This has previously been used to assemble nanoparticles in a number of different studies [6][7][8][9] but only recently to investigate the enhancement of the SERS effect.…”
Section: Mixed Metal Nanoparticle Assembly and The Effect On Surface mentioning
confidence: 99%
“…The nanoparticles showed positive charge in pH < 10 indicating that NH 2 groups transformed into NH + 3 group on the nanoparticle surface. The zeta potential was more than +30 mV that was considered as the threshold value for electrostatic stabilization [19]. Magnetization results ( figure 3(d)) indicated paramagnetic behavior at 300 K and antiferromagnetic behavior with sigmoid curve at 5 K [20,21].…”
Section: Physical Characterization Of Nanoparticlesmentioning
confidence: 97%
“…This indicated that NH 2 groups on nanoparticle's surface transformed into NH 3 + group. The zeta potential was more than +30 mV that was considered as the threshold value for electrostatic stabilization [32].…”
Section: Physical Characterization Of Functionalized Mnpmentioning
confidence: 99%